Pendidikan Islam Menuju Masyarakat Madani di Era Globalisasi (Suatu Ikhtiar Menghadapi Tantangan Masyarakat Ekonomi Asean/MEA) - Eko Nursalim (AT-TURATS, 2016)
Education is a human effort to buil his personality based on community values and culture. Even the simplest community has education process. Islam education concept building and increasing human quality and moeslim community in globalization era refer to Al-Quran and As-sunnah as the true resources. So that, Islam education should be able to deliver human as madani community whose has hard skill and soft skill packaged by Islamic values that ready to face all the chllanges in ASEAN Econimic community (MEA) with strategic steps to actualize relevant islam identity in every era.